Mechanical and thermal properties of halloysite nanotubes reinforced poly(ethylene terephthalate)/Polycarbonate nanocomposites - Nurul Ain Jamaludin, 1989-; Azman Hassan, supervisor; Norhayani Othman, supervisor; Fakulti Kejuruteraan Kimia (2015)
Thesis (Sarjana Kejuruteraan (Polymer)) - Universiti Teknologi Malaysia, 2015